Translation Ideology in the Indonesian-English Translation of Culture-Bound Words in Okky Madasari’s Novel Entrok - Afnani Salwa Nisrina; Issy Yuliasri; Widhiyanto (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the translation of culture-bound words in Okky Madasari’s novel Entrok and its English translation, The Years of the Voiceless. This research employs a descriptive qualitative method to identify the translation techniques used and to determine the dominant translation ideology applied in the translation process. The findings reveal that nine translation techniques were used in translating culture-bound words, with adaptation being the most frequently employed technique. The analysis also indicates that domestication is the predominant translation ideology, as most culture-bound words were translated in a way that makes them more accessible to the target language readers. However, some instances of foreignization were also found, particularly when preserving the original cultural meaning was necessary. This study contributes to the field of translation studies by providing insights into how culture-bound words are translated in literary works. Additionally, it has implications for translation education, as understanding these techniques and ideologies can benefit students and translators in dealing with cultural elements in translation.